Changes in Rates of Hospitalizations due to Cannabis Harms in Ontario, Canada Before the Legalization of Nonmedical Cannabis: Retrospective Population-level Study Between 2003 and 2017. Issue 3 (May 2022) - Zygmunt, Austin; Tanuseputro, Peter; Brown, Catherine; Lima, Isac; Rhodes, Emily; Myran, Daniel
Abstract : Objectives: To assess the burden of hospitalizations due to cannabis harms in Ontario, Canada before Canada's legalization of nonmedical cannabis. Methods: We conducted a retrospective population-level study that included all individuals living in Ontario between 2003 and 2017. We described patterns of hospitalizations due to cannabis harms in men and women by demographics, socioeconomic factors, and mental health comorbidities. We calculated annual crude rates of hospitalizations due to cannabis harms and assessed time trends using Poisson regression models. Results: There were 39, 092 hospitalizations due to cannabis harms among 32, 811 unique individuals. Annual hospitalizations due to a cannabis harm increased by 176% between 2003 and 2017 (1712 vs 4730), with increases noted for all age groups and sexes. Rates of hospitalizations due to cannabis harms were greater in young adults, low-income individuals, and those with mental health comorbidities. Overall, the rate of hospitalizations due to cannabis harms increased on average by 7.8% per year (95% CI 7.5–8.0). Women aged 15 to 24 experienced the largest average annual increase (12.2% per year, 95% CI 11.5 to 12.8). Conclusions: There are distinct patterns of hospitalizations due to cannabis harms in different priority populations. Young women aged 15 to 24 are a key demographic that is disproportionately burdened with a rapid increase in hospitalizations due to cannabis harms. Jurisdictions considering new approaches to cannabis control policy and addiction services should consider the rising burden of harms faced by youth and young adults when planning interventions.